Evliyâ Çelebi’nin Freng-pesend Resim Tutkusu - Nuran Tezcan (Cahiers Balkaniques)
Evliyâ Çelebi evidently became acquainted with European painting at an early age. Somewhat later, as he writes, he studied calligraphy with Güğümbaşı Mehemmed Efendi and nakş — i.e., painting — with Nakkaş Hükmizâde Alî Beg. He also informs us in several passages of the Seyahatnâme that he made pictures. Evliyâ was no adherent of the doctrine that making images is a sin in Islam. In his discussion of the painters (nakkaş) in the Istanbul guild parade he states that picture-making serves the glory of Islam and therefore that nakş is permitted.Observation and appreciation of works of art play a large role in the Seyahatnâme; they are an inseparable part of Evliyâ’s career as a traveler. Painting and architecture are the most important areas for his observation and appreciation of the “other.” In works of art, be they Islamic or non-Islamic, he recognized the qualifications of master artists (üstâd-ı kâmil) and tried to understand how they achieved success in their creative endeavor. Looking at art works belonging to the “other” and analyzing them, even interpreting them, became an important criterion for understanding the world of the “other” and its power.Although the definition of Freng / Frengistân in the Seyahatnâme cannot be established precisely, its usage more or less coincides with “European / Europe,” so the term provides a clue to how Evliyâ viewed Europe and European art. Combing through the contexts where the word occurs, we notice two trends, one negative — as in Freng-i pür-ceng (barbarian Franks), Freng-i bed-reng (evil Franks), Freng-i pür-reng (tricky Franks); one positive — as in Freng-pesend (pleasing to the Franks), the term used in the appreciation of architecture and painting.In the Seyahatnâme, Freng-pesend connotes Frankish (i.e., European) style or technique, Frankish taste, Frankish creativity. In Vienna, Kaschau, Korokonder (? – in Germany), Athens, Crete, Chios and Antalya, Evliyâ is amazed at the outstanding quality of certain paintings, statues and architectural monuments in “Frankish” style and technique and tries to grasp and convey this quality. The admiration and amazement he feels toward Frankish painting lead him to compare it with that of Mani, considered the greatest master of painting in the East, and his picture album known as Erjeng. In this way he tries to make concrete the creative power of Frankish painters by analogy to something in his own culture: üstâd-ı nakkâş-ı Fireng-i Mânî-i Erjeng (“painting master of the Franks like Mani of Erjeng”).In his evaluations of architectural works, Freng-pesend means “in accordance with Frankish style and taste,” while in painting it refers to colorful, miraculous images made with fine workmanship. He says that when confronted with such works, those who understand the art of painting bite their fingers in amazement. And he clearly expresses his opinion that European painting, which he equates with “Mani,” is superior to that of the East: “Indeed, when the Franks come to painting they outstrip the Indians and the Persians” (hakkâ kim Freng tasvîre geldikde Hind ü Acem’e gâlibdir).In Manya, Ali Paşa requests Evliyâ to make a picture of Zarnata castle that recently fell to the Ottomans. Evliyâ does this with paints of many colors, depicting Zarnata with all its buildings “in Frankish style” (Freng-pesend). He characterizes the painting he himself made as Freng-pesend and feels pride at this, saying that those who saw the buildings he drew would put finger to mouth in amazement. Using the concept of Freng-pesend as a criterion to judge his own work shows that in regard to painting he measures himself by the standard of Europe, whose superiority in this area he accepts.